FRONTAL FACIAL SYMMETRY DETECTION USING EIGENVALUE METHOD - Dewi Agushinta R.; Suryadi H. S.; Harya Iswara A.W. (JUTI: Jurnal Ilmiah Teknologi Informasi, 2008)
Facial symmetry is correspondence of face components on the both sides of face, left and right of a dividing line or about a center or an axis. Most of the research use face component like eyes, nose and ears component to identify facial symmetry. In this paper we suggest to add mouth as another face component to increase accuracy in facial symmetry detection. The results of facial symmetry detection are used for authentication process, analysis in medical, psychology and anthropology scope. By using MATLAB 7.1 we develop a program that can analyze face,asymmetry or not with utilizing eigenvalue. The contribution of this analysis is to know whether eigenvalue is suitable or not in analyzing facial symmetry. Keywords: Eigenvalue, Face Components, Facial Symmetry